Evolution of influenza A virus PB2 genes: implications for evolution of the ribonucleoprotein complex and origin of human influenza A virus. - Gorman, O T (1990)
Phylogenetic analysis of 20 influenza A virus PB2 genes showed that PB2 genes have evolved into the following four major lineages: (i) equine/Prague/56 (EQPR56); (ii and iii) two distinct avian PB2 lineages, one containing FPV/34 and H13 gull virus strains and the other containing North American avian and recent equine strains; and (iv) human virus strains joined with classic swine virus strains (i.e., H1N1 swine virus strains related to swine/Iowa/15/30). The human virus lineage showed the greatest divergence from its root relative to other lineages. The estimated nucleotide evolutionary rate for the human PB2 lineage was 1.82 x 10(-3) changes per nucleotide per year, which is within the range of published estimates for NP and NS genes of human influenza A viruses. At the amino acid level, PB2s of human viruses have accumulated 34 amino acid changes over the past 55 years. In contrast, the avian PB2 lineages showed much less evolution, e.g., recent avian PB2s showed as few as three amino acid changes relative to the avian root. The completion of evolutionary analyses of the PB1, PB2, PA and NP genes of the ribonucleoprotein (RNP) complex permits comparison of evolutionary pathways. Different patterns of evolution among the RNP genes indicate that the genes of the complex are not coevolving as a unit. Evolution of the PB1 and PB2 genes is less correlated with host-specific factors, and their proteins appear to be evolving more slowly than NP and PA. This suggests that protein functional constraints are limiting the evolutionary divergence of PB1 and PB2 genes. The parallel host-specific evolutionary pathways of the NP and PA genes suggest that these proteins are coevolving in response to host-specific factors. PB2s of human influenza A viruses share a common ancestor with classic swine virus PB2s, and the pattern of evolution suggests that the ancestor was an avian virus PB2. This same pattern of evolution appears in the other genes of the RNP complex. Antigenic studies of HA and NA proteins and sequence comparisons of NS and M genes also suggest a close ancestry for these genes in human and classic swine viruses. From our review of the evolutionary patterns of influenza A virus genes, we propose the following hypothesis: the common ancestor to current strains of human and classic swine influenza viruses predated the 1918 human pandemic virus and was recently derived from the avian host reservoir.